The effect of exercise intervention on inhibitory function in obese and overweight children and adolescents: a systematic review and meta-analysis - Aona Chen; Chenggen Guo; Shuhua Qu (BMC Pediatrics)
Abstract Background and objectives Obese and overweight children and adolescents exhibit significant deficits in inhibitory function compared to their typical-weight peers. There is a high variability in the effectiveness of exercise interventions on inhibitory function in obese and overweight children and adolescents, and clinical protocols lack consistency. This study aims to systematically review the effects of exercise interventions on inhibitory function in obese and overweight children and adolescents. Methods A systematic search was conducted on Web of Science, PubMed, Cochrane Library, EBSCO, WanFang Database, and China Knowledge Resource Integrated Database (CNKI) to gather randomized controlled trials (RCTs) examining the impact of exercise interventions on inhibitory function in obese and overweight children and adolescents. The search covered publications from January 2000 to January 8, 2024. Two researchers independently conducted a meta-analysis, screening the literature, extracting information, and assessing the methodological quality of the included studies. Results The analysis included 24 randomized controlled trials (RCTs) with a total of 1,247 participants. The meta-analysis showed that post-intervention improvements in inhibitory function were significantly greater in the experimental group compared to the control group (SMD = -0.65, 95% CI = -1.01 to -0.29, p < 0.01), indicating a medium effect size. Subgroup analyses indicated that open motor skills (SMD = -0.73, 95% CI = -1.20 to -0.27, p < 0.01), moderate intensity (SMD = -0.80, 95% CI = -1.37 to -0.23, p < 0.01), and long-term regular exercise (SMD = -1.04, 95% CI = -1.47 to -0.62, p < 0.01) were significantly more effective than controls in improving inhibitory function. Both small exercise (SMD = -1.60, 95% CI = -2.25 to -0.94, p < 0.01) and large exercise volume (SMD = -0.85, 95% CI = -1.33 to -0.37, p < 0.01) outperformed the control group. Additionally, Stroop, Flanker, and Go/No-go tasks (SMD = -0.88, -0.62, 0.73, 95% CI = -1.43 to -0.32, -1.09 to -0.15, 0.20 to 1.25, p < 0.01) effectively assessed inhibitory function in obese and overweight children and adolescents. Conclusion Exercise can improve the inhibitory function of obese and overweight children and adolescents. The effectiveness of this intervention is influenced by exercise type, intensity, and duration. Long-term regular exercise involving open motor skills and moderate intensity yields better results in enhancing the inhibitory function of obese and overweight children and adolescents. Systematic review registration The protocol of this systematic review was registered with INPLASY. The protocol ID was INPLASY202450061.